MANAGEMENT OF HIV/AIDS INFECTION IN PREGNANCY - Dewati, Endah; Nasronudin, Nasronudin (Indonesian Journal of Tropical and Infectious Disease, 2014)
Twenty years since identified for the first time, the disease of HIV/AIDS spread and cause greater damage than the previous prediction. According to the Director General of P2M and Environmental Sanitation Department of Health by the end of 1999, there were 1066 people in Indonesia who are infected with HIV even though this must be realized that the rate is still far lower than the actual numbers, because there are many cases of HIV infection reported in addition to energy awareness health of the possibility of HIV infection has not been evenly distributed. Management of HIV infection/AIDS in pregnancy is done in time of antepartum, intrapartum and post partum, for mother and the baby, in general and specific. The important matters include the use of ART, nutrition and psychological support. Prevention and management of opportunistic infections to PWHA are not different with that of non pregnant woman. However, it is not routinely advised because of drug toxicity.